Management of Nonmalignant Portal Vein Thrombosis in Cirrhosis - Francisco Capinha; Carlos Noronha Ferreira (GE: Portuguese Journal of Gastroenterology, 2023)
Nonmalignant portal vein thrombosis (PVT) is a common complication of cirrhosis especially at the stage of decompensations. The diagnosis of PVT in cirrhosis is often incidental and it may be detected during routine semestral abdominal ultrasound with Doppler during screening for hepatocellular carcinoma or during hospitalization for decompensated cirrhosis. After detection of PVT on abdominal ultrasound, it is important to evaluate patients with cross-sectional imaging to determine the age of thrombus, whether acute or chronic, the extent and degree of luminal occlusion of the portal vein, and to rule out hepatocellular carcinoma or other underlying malignancy. Factors influencing management include the degree and extent of luminal occlusion of PVT, potential listing for liver transplantation, and portal hypertension (PHT) complications such as variceal hemorrhage and refractory ascites, severity of thrombocytopenia, and other comorbidities including chronic kidney disease. Anticoagulation is the most common therapeutic option and it is specially indicated in patients who are candidates for liver transplantation. Interventional procedures including transjugular intrahepatic portosystemic shunt (TIPS) placement and mechanical thrombectomy may be used on a case-by-case basis in patients with contraindications or adverse events related to anticoagulation, who develop worsening PVT while on anticoagulant therapy, or have chronic PVT and PHT complications that are not manageable medically or endoscopically.